2018
DOI: 10.1002/epi4.12103
|View full text |Cite
|
Sign up to set email alerts
|

Early EEG predicts poststroke epilepsy

Abstract: SummaryObjectiveElectroencephalography (EEG) can identify biomarkers of epileptogenesis and ictogenesis. However, few studies have used EEG in the prediction of poststroke seizures. Our primary aim was to evaluate whether early EEG abnormalities can predict poststroke epilepsy.MethodsA prospective study of consecutive acute anterior circulation ischemic stroke patients, without previous epileptic seizures, who were admitted to a stroke unit over 24 months and followed for 1 year. All patients underwent standar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
65
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(73 citation statements)
references
References 43 publications
2
65
2
Order By: Relevance
“…Electroencephalography adds value to early diagnosis, outcome prediction, patient selection for treatment, clinical management and seizure detection in acute stroke . It can also be very helpful in the early evaluation of poorly defined post‐stroke focal neurologic symptoms and seizure mimics .…”
Section: Electroencephalography In Stroke‐related Epilepsymentioning
confidence: 99%
See 2 more Smart Citations
“…Electroencephalography adds value to early diagnosis, outcome prediction, patient selection for treatment, clinical management and seizure detection in acute stroke . It can also be very helpful in the early evaluation of poorly defined post‐stroke focal neurologic symptoms and seizure mimics .…”
Section: Electroencephalography In Stroke‐related Epilepsymentioning
confidence: 99%
“…The most frequent EEG findings in acute stroke are focal slowing corresponding to side of infarct and diffuse slowing, both of which are associated with low risk for seizures . Focal spikes, sharp waves and periodic patterns including lateralized periodic discharges are associated with increased risk of seizures (STRE) .…”
Section: Electroencephalography In Stroke‐related Epilepsymentioning
confidence: 99%
See 1 more Smart Citation
“…Andrade et al investigated the role of sleep-wake disturbance in EPG and found that there is a decrease of the dominant frequency and the duration of sleep spindles in a traumatic brain injury epilepsy model with generalized seizures [9]. Bentes et al found that in stroke patients, the asymmetry in the background activity with the occurrence of IEDs are independent indicators of post-stroke epilepsy in the first year after stroke [10]. Sheybani et al found that in a mouse model of epilepsy with kainate injection, the spatial propagation of a subgroup of spikes across the brain can be a reliable indicator of EPG as well as epilepsy in the chronic phase [30].…”
Section: Eeg-based Biomarkers Of Epileptogenesismentioning
confidence: 99%
“…The global aim of this thesis was to use the clinical model of acute ischemic cerebrovascular disease to study the value of EEG in the differential diagnosis of transient neurological symptoms, in the diagnosis and prediction of poststroke seizures and epilepsy, as well as to analyze if electroencephalographic abnormalities and/or epileptic seizures are independent predictors of an anterior circulation ischemic stroke outcome, as described in this article published in Epilepsia Open . Furthermore, because the gold standard of acute stroke care (namely intravenous alteplase treatment) is associated with a reduction of mortality and incapacity of treated patients with possible consequences in poststroke seizure frequency, but a proconvulsive and an epileptogenic effect of alteplase has also been described, we aim to test the hypothesis that ischemic stroke patients treated with intravenous alteplase have a different frequency of epileptic (clinic and/or electroencephalographic) manifestations compared to nontreated patients .…”
Section: What Next Steps In Epilepsy Research Are You Taking and Whatmentioning
confidence: 99%